Gibberellins orchestrate panicle architecture mediated by DELLA–KNOX signalling in rice. Issue 11 (24th August 2021) - Su, Su; Hong, Jun; Chen, Xiaofei; Zhang, Changquan; Chen, Mingjiao; Luo, Zhijing; Chang, Shuwei; Bai, Shaoxing; Liang, Wanqi; Liu, Qiaoquan; Zhang, Dabing
Summary: Panicle architecture is a key determinant of grain yield in cereals, but the mechanisms governing panicle morphogenesis and organ development remain elusive. Here, we have identified a quantitative trait locus ( qPA1 ) associated with panicle architecture using chromosome segment substitution lines from parents Nipponbare and 9311. The panicle length, branch number and grain number of Nipponbare were significantly higher than CSSL‐9. Through map‐based cloning and complementation tests, we confirmed that qPA1 was identical to SD1 ( Semi Dwarf1 ), which encodes a gibberellin 20‐oxidase enzyme participating in gibberellic acid (GA) biosynthesis. Transcript analysis revealed that SD1 was widely expressed during early panicle development. Analysis of sd1/osga20ox2 and gnp1/ osga20ox1 single and double mutants revealed that the two paralogous enzymes have non‐redundant functions during panicle development, likely due to differences in spatiotemporal expression; GNP1 expression under control of the SD1 promoter could rescue the sd1 phenotype. The DELLA protein SLR1, a component of the GA signalling pathway, accumulated more highly in sd1 plants. We have demonstrated that SLR1 physically interacts with the meristem identity class I KNOTTED1‐LIKE HOMEOBOX (KNOX) protein OSH1 to repress OSH1‐mediated activation of downstream genes related to panicle development, providing a mechanistic link between gibberellin and panicle architecture morphogenesis.